Perlindungan Hukum terhadap Pemilik Saham Selaku Penjual atas Pembatalan Akta Jual Beli Saham oleh Pengadilan - Nizar Nizar; Dhoni Martien; Amelia Nur Widyanti (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
Share trading in limited liability companies that does not comply with the procedures for transferring share ownership under the Company Law may lead to legal disputes, particularly unpaid share transactions. This study examines the annulment of share sales by the court to protect the seller’s interests when the buyer defaults, based on Article 1320 of the Indonesian Civil Code. The case analyzed is District Court Decision No. 6 K/Pdt.G/2017. Legal protection for sellers includes clauses concerning legal subjects and objects, price, payment methods, share transfer, and dispute resolution in accordance with Articles 1457 and 1513 of the Civil Code. Using a normative juridical method with statutory, conceptual, analytical, and case approaches, the study concludes that default in share sale agreements may nullify ownership rights. Therefore, strict sanctions and legal remedies through the court are essential to safeguard shareholders’ rights.